Species composition of dry-temperate forest as an important habitat for wildlife fauna species - Rajpar, M. N.; Ozturk, M.; Altay, V.; Ullah, S.; Ullah, A.; Martin, C.O.; Gucel, S.; M. Zakaria (Triveni Publishers, 2020)
Aim: To determine the present species composition and diversity in dry temperate forest ecosystem, especially trees, shrubs, ground cover, birds, reptiles and mammals.